2019
DOI: 10.1093/eep/dvz023
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenome-wide association of father’s smoking with offspring DNA methylation: a hypothesis-generating study

Abstract: Epidemiological studies suggest that father’s smoking might influence their future children’s health, but few studies have addressed whether paternal line effects might be related to altered DNA methylation patterns in the offspring. To investigate a potential association between fathers’ smoking exposures and offspring DNA methylation using epigenome-wide association studies. We used data from 195 males and females (11–54 years) participating in two population-based cohorts. DNA methylation was quantified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…In a study by Svanes et al [ 25 ], the age of smoking onset in the parents was an important risk factor for asthma in their offspring, even after adjustment for the number of cigarettes they had smoked before conception. Moreover, a recent epigenome-wide association study showed associations between pre-conception paternal smoking and DNA methylation characteristics in adult and adolescent offspring—independent of the amount smoked [ 49 ]. Our findings suggest that the same patterns may be present for air pollution exposures as for smoking exposures.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Svanes et al [ 25 ], the age of smoking onset in the parents was an important risk factor for asthma in their offspring, even after adjustment for the number of cigarettes they had smoked before conception. Moreover, a recent epigenome-wide association study showed associations between pre-conception paternal smoking and DNA methylation characteristics in adult and adolescent offspring—independent of the amount smoked [ 49 ]. Our findings suggest that the same patterns may be present for air pollution exposures as for smoking exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Initial epigenetic studies by our group have shown that male cannabis use, and male rat exposure to THC, cause widespread DNA methylation changes in sperm 16 . Furthermore, others have shown that cigarette smoking significantly alters DNA methylation patterns in male sperm 63 , 64 , showing that there are also genome-wide epigenetic effects of this exposure. The significance and impact of these changes in sperm on offspring health and development are only beginning to be explored—yet results may provide important information and critical opportunities for preventive interventions to reduce risk to future children.…”
Section: Discussionmentioning
confidence: 99%
“…The father’s health prior to conception and the exposures he incurs during this time may also impact offspring health and development. Studies show that exposure to cannabis and tobacco products alter sperm DNA methylation 15 17 . There is an urgent need to determine whether these effects are heritable, especially given that men are the predominant cannabis and tobacco product consumers 18 – 20 , and their use is increasing 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Although increased adipose tissue does not necessarily translate into metabolic abnormalities, both BMI and FMI are regarded important determinants of metabolic health at the population level [ 40 , 41 ], and childhood adiposity has been reported to be associated with increased risk of adult type 2 diabetes mellitus [ 42 ]. In a recent epigenome-wide association study, we found that adult offspring with smoking fathers had differential methylation in regions related to innate immune system pathways and fatty acid bio-synthesis [ 43 ]. These are inflammatory signalling pathways and metabolic signals that have been linked to obesity [ 44 ].…”
Section: Discussionmentioning
confidence: 99%